Continuing professional development in Chile: A case study. Issue 2 (2nd July 2016) - Garcia, Jenniffer; Copley, Jodie; Turpin, Merrill; Chien, Chi-Wen; Peña, Natalia
ABSTRACT: Continuing professional development (CPD) helps achieve quality practice founded on sound clinical reasoning and evidence. While CPD is a core component of registration in Anglophone countries, access to high-quality CPD may be limited in developing countries. Chile, a developing country graduating an increasing number of occupational therapists, provides a useful case for exploring CPD. Ten paediatric occupational therapists were interviewed regarding their access to CPD.Findings : CPD in Chile is accessed mainly through available short-term activities that cover a limited range of topics. Informal professional networks are heavily used. As Chilean occupational therapists face barriers accessing research databases and text books, social media is a common source of information.Conclusions : For developing countries, language barriers can restrict access to professional knowledge and opportunities to participate in global networks and discussions regarding contemporary occupational therapy practice. CPD can be instrumental in promoting research culture and facilitating culturally relevant evidence-informed practice.